Evaluation of the Quality of Solder Joints within Silicon Solar Modules Using Magnetic Field Imaging. Issue 6 (6th January 2021) - Kaufmann, Kai; Lausch, Dominik; Lin, Chia-Mei; Rudolph, Maik; Hahn, Daniel; Patzold, Markus
Abstract : Solar cells and modules are already a mature technology in mass production. It is critical to optimize and to systematically monitor their performance. The introduction of automated soldering processes and the increasing usage of novel contacting schemes can cause harmful defects, e.g., missing and defective contacts, and, thus, affect the electrical performance of solar modules after production or in field usages. Herein, magnetic field imaging (MFI) is utilized to do a non‐destructive, quantitative analysis of the modules to investigate the quality of the soldering contacts. In detail, the cross connector, interconnector, and rear‐side pads are investigated. The typical in‐field observed defects are presented. For the first time, the quality of rear‐side pads under operation is studied in detail. It is shown that 1) directly after production, the current conduction takes place not only via the rear pads but also via the press‐on contact between the bare aluminum and the rear‐side ribbons; 2) an off‐centered ribbon on the pad leads to abnormal current distribution; and 3) single rear‐side pad breaks as a function of thermal cycles due to thermo‐mechanical stress. Abstract : Magnetic field imaging (MFI) is used to assess the contact quality in solar modules. Various critical areas in the solar module are considered, including cross connectors, interconnectors, and the rear‐side soldering. It is shown that broken connectors and missing solder joints can be detected reliably. Furthermore, the influence of thermal cycling on the presence of solder contacts is discussed.